2018
DOI: 10.2478/jtim-2018-0033
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between MELD and UNa/K ratio in predicting renal dysfunction in cirrhotic patients

Abstract: BackgroundRenal dysfunction is one of the dreaded complications of cirrhosis. MELD is a validated chronic liver disease (CLD) severity scoring system. Urinary (U) Na/K ratio closely correlates with renal dysfunction in terms of low GFR in cirrhotic patients.Patients and MethodsAll consecutive patients with decompensated cirrhosis between the age of 18 to 70 years, of either gender, presenting in the outpatients’ department of Sindh Institute of Urology and Transplantation, Karachi, from June 2015 to June 2017 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
1
0
1
Order By: Relevance
“…Our study found that reduced sodium excretion, either as spot urine Na/K ratio or FENa, was related to more severe liver disease, i.e., high MELD-Na score or high CTP score. Similarly, Iqbal J et al found that a high MELD score was associated with low urine Na/K ratio [15] . da Silva OM et al found that poor sodium excretion group presented higher MELD score [16] .…”
Section: Discussionmentioning
confidence: 92%
“…Our study found that reduced sodium excretion, either as spot urine Na/K ratio or FENa, was related to more severe liver disease, i.e., high MELD-Na score or high CTP score. Similarly, Iqbal J et al found that a high MELD score was associated with low urine Na/K ratio [15] . da Silva OM et al found that poor sodium excretion group presented higher MELD score [16] .…”
Section: Discussionmentioning
confidence: 92%
“…La puntuación MELD/Na es un sistema de puntuación para acceder a la gravedad de la enfermedad hepática crónica utilizando valores como bilirrubina sérica, creatinina sérica y el índice internacional normalizado de tiempo de protrombina y sodio, para predecir la supervivencia. También es un puntaje utilizado para determinar la necesidad para trasplante hepático en los pacientes cirróticos, MELD > 15 puntos se considera paciente tributario a evaluación para trasplante hepático [47,48].…”
Section: Otras Terapiasunclassified